Supervisi Humas dan Ketatausahaan Pendidikan - Dhea Musdhalifa; Muhammad Syaifudin (LPPM Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2023)
ABSTRACT The educational process is an interaction process that is carried out where the process aims to improve or add to the knowledge possessed by students. In addition, the educational process also aims to provide personality values ​​to students as well as life skills that are possible to have. To achieve this educational goal, the school cannot be separated from its relationship with the community. In a simple relationship can be interpreted as a process of communication. Or in other words a process of conveying news from one person to another. The community here can be in the form of parents, students, agencies or organizations in the community. Meanwhile, educational officials can be in the form of school principals, teachers, and staff related to the school. It can be concluded that the relationship between the school (educational apparatus) and the community is based on cooperation, not one-sided, but a reciprocal relationship in order to achieve the expected educational goals. Administration is a part of the school that functions as a support for teaching and learning activities so that they run smoothly according to what has been planned and can be achieved as desired. With the development of the era that is now better known as the era of globalization, administrative functions must be improved. Administration is important because administration can help and facilitate other subsystems such as student affairs, curriculum, personnel administration, and others